Habitat fragmentation and its lasting impact on Earth’s ecosystems - Haddad, Nick M.; Brudvig, Lars A.; Clobert, Jean; Davies, Kendi F.; Gonzalez, Andrew; Holt, Robert D.; Lovejoy, Thomas E.; Sexton, Joseph O.; Austin, Mike P.; Collins, Cathy D.; Cook, William M.; Damschen, Ellen I.; et al. (Science advances, 2015)
Urgent need for conservation and restoration measures to improve landscape connectivity. We conducted an analysis of global forest cover to reveal that 70% of remaining forest is within 1 km of the forest’s edge, subject to the degrading effects of fragmentation. A synthesis of fragmentation experiments spanning multiple biomes and scales, five continents, and 35 years demonstrates that habitat fragmentation reduces biodiversity by 13 to 75% and impairs key ecosystem functions by decreasing biomass and altering nutrient cycles. Effects are greatest in the smallest and most isolated fragments, and they magnify with the passage of time. These findings indicate an urgent need for conservation and restoration measures to improve landscape connectivity, which will reduce extinction rates and help maintain ecosystem services.